Sistema de gestión de infraestructura de red basado en software libre, para la Empresa Eléctrica Regional Norte EMELNORTE S.A - Fray Buestán, Victoria Jazmín (2025)
The proposed project aims to implement a Network Infrastructure Management System based on open-source software at Empresa Eléctrica Regional Norte S.A., with the objective of aligning the system with industry best practices, such as the FCAPS model, to ensure a robust and standardised solution. For this reason, the focus of this project was not only to improve the operational efficiency of the company, but also to lay the foundation for a more agile, secure and scalable network management in the future, thus aiming for a comprehensive and sustainable improvement. This project is expected not only to improve the operational efficiency of the company, but also to lay the foundations for a more agile, secure and scalable network management in the future. In this way, a comprehensive and sustainable improvement is aimed for. The implementation of this system represents an investment in technology and a commitment to operational excellence, information security and customer satisfaction. This effort is key to the sustainable future of the company and the quality of service offered to its users. Technology becomes a strategic pillar. Finally, it is recommended to consider this project as a strategic investment in technology, which will lay the foundations for a more agile, secure and adaptable network management to the changing needs of the organisation.